Did Neandertals have large brains? Factors affecting endocranial volume comparisons. Issue 4 (16th August 2020) - VanSickle, Caroline; Cofran, Zachary; Hunt, David
Abstract: Objectives: Common wisdom in paleoanthropology is that Neandertals had bigger brains than recent humans. Here we tested the hypothesis that there is no difference in brain size between Neandertals and recent humans while accounting for methodological variation and the makeup of both the Neandertal and recent human samples. Materials and Methods: We examined endocranial volume (ECV) derived from virtually reconstructed endocasts of 11 Neandertals, six of which had associated femoral head diameters (FHD). Our recent human comparative dataset consisted of virtually measured ECV and associated FHD from 94 recent humans from the Robert J. Terry Anatomical Collection (63 male, 31 female). ECV of Neandertals and recent humans was compared using bootstrap resampling, repeating the analysis for two groupings of Neandertals (all and classic) and for three groupings of recent humans (all, males, and females). To examine brain size scaling, we completed an ordinary least squares regression of log (ECV) against log (FHD) for Neandertals and recent humans. Results: The results of the bootstrap resampling analyses indicated that Neandertals only had significantly larger ECV when compared with recent human females. The regression between ECV and FHD suggested that Neandertals fall within the range of variation for larger humans. Discussion: Our results demonstrate that Neandertals do not have uniquely large brains when compared with recent humans. Their brain size falls in the large end of the recent human range of variation, but does not exceed it. These results have implications for future research on Neandertal encephalization.